Lecturers’ Compliance With Quality Assurance Mechanisms in Public Universities in Delta State: Focusing on Punctuality, Regular (Asian Journal of Social Science Studies, 2019)
The study investigated the extent to which lecturers comply with quality assurance mechanisms in public universities in Delta State. Two objectives, two research questions and two hypotheses guided the study. The descriptive survey research design was adopted. The population of the study consisted of 1,299 lecturers and 6,826 students from the public universities in Delta State. A sample of 260 lecturers and 409 students representing 20% and 6% respectively of the population which was obtained using the proportionate random sampling technique was used. The instrument for data collection was the researchers made questionnaire titled “Compliance with Quality Assurance Mechanisms Questionnaire (CQAMQ). The Cronbach Alpha method was used to determine the internal consistency of the items and it yielded a result of 0.78 and 0.79. The researchers and two assistants distributed 669 copies of the questionnaire and successfully collected 628 copies of the questionnaire administered. The research questions were analyzed using the mean, standard deviation and rank order statistics, while the hypotheses were tested using z-test at 0.05 level of significance. It was found that lecturers’ in public universities in Delta State complied with punctuality and regular attendance to lectures and adhered to the course outline to a high extent. Based on the findings, it was concluded that lecturers compliance with the quality assurance mechanism of punctuality and regular attendance ,adherence to the course outline is high, it was recommended that the university management should encourage lecturers to adhere to the course outline through collegial supervision, and ensure that the course outlines to be used are submitted to the head of departments, the university management should initiate a reward system whereby lecturers that are always punctual and regular in attendance to lectures are given prizes and recognition.